“When the problem is not inclusion”: Limitations and possibilities in the implementation of an inclusive approach in education: The case of the IE Jose Galvez, Comas - Sanchez De La Flor, Grecia (2022)
This article addresses the issue of educational inclusion by critically reviewing regulations and theoretical discussions on the subject. The research process focuses on the implementation of inclusion politics in an educational institution, drawing attention to the contradictions between the different subjectivities and beliefs of the educational community about disability and its influence in the inclusion of students with disabilities. The main findings expose the interpretation of the inclusion approach given by principals and teachers in order to respond to the obligations set by the sector’s authority. However, they also clearly show the flaws and limitations of the sector in including without stigmatizing, in and out the classroom, while prevailing pedagogical practices according to the possibilities the institution in spite of the inclusive discourse. Incidentally, the article also examines the educational management and its importance to tackle change in education for students with said condition, the active role of the educational community to articulate in the process, and identifies valuable contributions for a new interpretation of the problem.